Emerson and the reconstruction of pragmatism (Философский журнал | Philosophy Journal, 2019)
Beginning in the nineteenth century with writings of Ch. S. Peirce, William James, and John Dewey, pragmatism fell into eclipse during World War II with the influx of logical positivism. But W. V. O. Quine and Wilfrid Sellars attacked logical positivism at its foundations in analyticity and the simply given, and then pointed contemporary philosophy back to classical pragmatism, and so began the revival. Following Quine and Sellars, Rorty in his brilliant Philosophy and the Mirror of Nature stamped pragmatism back into contemporary philosophy, reestablishing James and Dewey as central figures. Today the movement of pragmatism is once again in full-swing, with major pragmatist philosophers, like Richard Shusterman and Russell Goodman, engaging the tradition and reconstructing its background in Ralph Waldo Emerson’s transcendentalism, and the founders like Benjamin Franklin and Thomas Jefferson.